RAB18 regulates extrahepatic siRNA-mediated gene silencing efficacy - Jiamiao Lu; Jasper Lee; Eric Yuan; Devin L. Wakefield; Matt Kanke; Danielle Pruitt; Jose Barreda; Ingrid C. Rulifson; Jiansong Xie; John Ferbas; Jason Long; Bryan Meade; et al. (Elsevier, 2024)
Small interfering RNAs (siRNAs) hold considerable therapeutic potential to selectively silence previously "undruggable" disease-associated targets, offering new opportunities to fight human diseases. This therapeutic strategy, however, is limited by the inability of naked siRNAs to passively diffuse across cellular membranes due to their large molecular size and negative charge. Delivery of siRNAs to liver through conjugation of siRNA to N-acetylgalactosamine (GalNAc) has been a success, providing robust and durable gene knockdown, specifically in hepatocytes. However, the poor delivery and silencing efficacy of siRNAs in other cell types has hindered their applications outside the liver. We previously reported that a genome-wide pooled knockout screen identified RAB18 as a major modulator of GalNAc-siRNA conjugates. Herein, we demonstrate RAB18 knockout/knockdown efficaciously enhances siRNA-mediated gene silencing in hepatic and extrahepatic cell lines and in vivo. Our results reveal a mechanism by which retrograde Golgi-endoplasmic reticulum (ER) transport and the intracellular lipid droplets (LDs) positively regulate siRNA-mediated gene silencing.